TEKNIK KONSERVASI LAHAN MENGGUNAKAN METODE KANOPI TANAMAN LABU SIAM (Sechium Edule) DI DESA SUMBER BRANTAS BATU MALANG - Talifatim M; Anggraeni Hadi P; Risfa Nurrohman; Evi Dwi Safitri; Pitaloka, Dyah (Universitas Islam Balitar, 2019)
Chayote (Sechiumedulesp) is gourd family (Cucurbiatea), this plant leaves tightly closed the planting area, grows on the ground or rather climbs, and is usually cultivated in the yard.Land conservation using the canopy cover method is one of the efforts made to save the environment.The change of land stretch from closed forest to open agricultural area and residential area in Tulungrejo Village, BumiadjiSubdistrict, Batu City is potential land degradation due to erosion caused by extreme rainfall due to the impact of climate change. This study aims to determine the difference in the amount of erosion caused by rain wateron open land and closed land conservation using the Chayote plant canopy.This research was conducted from September to December 2018. The research location was in Tulungrejo Village, BumiadjiBatu District, East Java.The study began by making a 1x1 m2 water-holding pot in an open areaand areas with canopy cover of Chayote plants.The treatment in this study was repeated three times, with 5 duration of rain each 15 minutes later. The treatments were E1 = 30, minutes, E2 = 45 minutes, E3 = 60 minutes, E4 = 75 minutes and E5 = 90 minutes. The results showed significantly different at E5,the treatment of rain simulation for 90 minutes duration in an open area without canopy cover of the conjoined Chayote plant, the highest erosion reaches 121 kg / ha,while the area using land cover with canopy of Chayote plant statistic showed a significant difference in all treatments with the amount of erosion in the duration of 90 minutes 89 kg / ha.